2011 International Conference on Technologies and Applications of Artificial Intelligence 2011
DOI: 10.1109/taai.2011.55
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Belief State Estimation, with Application to Mines

Abstract: Abstract-Estimating the belief state is the main issue in games with Partial Observation. It is commonly done by heuristic methods, with no mathematical guarantee. We here focus on mathematically consistent belief state estimation methods, in the case of one-player games. We clearly separate the search algorithm (which might be e.g. alpha-beta or Monte-Carlo Tree Search) and the belief state estimation. We basically propose rejection methods and simple Monte-Carlo Markov Chain methods, with a time budget propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…considering also moves with non minimal probability of mine) can bring an improvement; but we have no proof. Also we have no proof that always playing in the corner for the first move is a good idea; it is known as a good heuristic, but maybe in some cases there are better moves (with the rule "first move is a 0", it is mathematically proved that the center is a good move in some cases; see [3]). Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…considering also moves with non minimal probability of mine) can bring an improvement; but we have no proof. Also we have no proof that always playing in the corner for the first move is a good idea; it is known as a good heuristic, but maybe in some cases there are better moves (with the rule "first move is a 0", it is mathematically proved that the center is a good move in some cases; see [3]). Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most classical approach for MineSweeper is based on Constraint Satisfaction Problems [14], as in Section 2.2: this provides a provably correct estimate of the belief state, and then classically after CSP one plays the covered location with least probability of being a mine. However, [3] has shown that this approach is suboptimal; there are situations, as in Fig. 2, where some moves with minimum probability of mines are nonetheless suboptimal moves.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations